The Early Muslim (The Arab) Contribution to the Development of Historiographical Traditions and Methods: A Critical Appraisal - Humera Naz (JSSH, 2023)
This article aims to highlight impacts and contribution of the early Muslims (The Arabs) to the field of historiography in terms of different traditions and methods. The early Muslims or the Arab contribution is significant for the genesis and introduction of some emerging trends and traditions in this field. This research is fundamentally based upon analysis of the early Muslim historical literature which offers an overview of the sirah, hadith, maghazi literature concerning the characteristics adopted from the pre-Islamic historical traditions. The paper explores the genesis and major trends set up during the formative phase of early Muslim (The Arab) historiography in terms of authentication and assessment of historical data. The paper tries to highlight some emerging categories in history introduced by the early Muslim historians besides the non-Arab (the Persian) contribution in the field of history writing.